Fullmetal alchemist. 11 - Arakawa, Hiromu, 1973- (Viz Media, 2007)
When an alchemical ritual goes awry causing Edward Elric to lose limbs and his brother to become trapped in a suit of armor, Edward begins a quest to recover the one thing that can restore them, the legendary Philosopher's Stone.